STUDI REDUKSI BANJIR DENGAN KOLAM RETENSI PADA SUNGAI-SUNGAI PARALEL - Rakhmat Yusuf (Universitas Teuku Umar, 2022)
Flood in Ujungberung region occurs when rainy season. The location of the Ujungberung region is in the Bandung basin area from the upstream river originating at the Mount Manglayang. The impact of floods that occur is disrupting the drainage flow, settlement, traffic and economic land use such as markets, and agriculture in the region. The government has made some prevention efforts by constructing three Retention Basin on the Cinambo River, Cipamulihan River, and Cilameta River. There isn’t analysis on how much the optimal reduction in flood discharge and reservoir volume. In this study using a quantitative approach and descriptive method. Retanding basin analysis is based on the 25-years hydrological flood discharge using the Snyder method HEC-HMS v4.3 software. From the results of the Retention Basin modeling, it was found that in the Cinambo River with the initial discharge of Q25 is 37.70 m3/sec become 11.10 m3/sec can be reduced by 70.56 % with an optimal storage volume of 143,300 m3, in the Cipamulihan River with the initial discharge of Q25 is 19.20 m3/sec become 8.10 m3/sec can be reduced by 57.81 % with an optimal storage volume of 143,300 m3, and in the Cilameta River with the initial discharge of Q25 is 13.40 m3/sec become 9.3 m3/sec can be reduced by 30.60% with an optimal storage volume of 23,100 m3. If the Retention Basin planned to be carried out with an optimal storage volume, it must be adjusted to the available retention land area and with a required dimension.